PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE JIGSAW TERHADAP KEMAMPUAN KONEKSI MATEMATIKA SISWA SMP - Nurdiana, Aty (Epsilon: Jurnal Pendidikan Matematika, 2021)
The problem in this study is related to the low ability of students'mathematical connections. Therefore, the purpose of this study was to determinethe effect of the Jigsaw Cooperative learning model on the mathematicalconnection abilities of class VIII students in the even semester of SMP Negeri 3Bandar Lampung in the 2020/2021 school year. This study uses experimentalmethods, as well as data analysis using parametric statistical formulas. Thepopulation in this study were all students of class VIII SMP Negeri 3 BandarLampung which consisted of 10 classes with a total of 314 students, while thesample was taken 2 classes, namely class VIII B as the experimental class whichamounted to 35, and class VIII A as the control class which amounted to 33 Thesample was taken using the Cluster Random Sampling technique. To determine thestudents' mathematical connection ability, it was measured using a test in the formof an essay as many as 5 questions which had been tested for validity and reliability.Hypothesis testing in this study used the t-test formula. From the results ofhypothesis testing using the t-test statistical formula, the value of t hit = 2.47 isobtained. From the t distribution table at a significant level of 5%, it is known thatt daf = ????(1âˆ’????)= 1.67, which means that t hit > t daf is 2.47 > 1.67, so it can beconcluded that there is an effect of the Jigsaw learning model on the mathematicalconnection abilities of class VIII students in the even semester of SMP Negeri 3Bandar Lampung in the 2020/2021 school year. This situation can also be seenfrom the average value of students' mathematical connection abilities where theexperimental class has an average value of 77.37 and the control class has anaverage value of 68.67.Keywords: Jigsaw cooperative type, mathematical c